The influence of consumer complaint behaviour on relationship quality among Malaysian mobile phone services subscribers: complainers versus non-complainers - A. Rahman, Mohd Khirzan Badzli; Haron, Sharifah Azizah; Paim, Laily; Osman, Syuhaily; Othman, Abdul Kadir (2016)
Mobile phone service subscribers in Malaysia have been increasing tremendously. However, the number of complaints received with regard to mobile phone services is small as compared to the number of subscribers. Evidently complaining is one of the consumer behaviours which provides significant impact to organisations as well as to complainers or consumers. Studies on Consumer Complaining Behaviour (CCB) are continuously carried out due to its importance. Although, CCB has extensively been studied in various countries and industries, limited studies are found investigating the relationship between CCB and relationship quality. Therefore, this study was conducted to reduce the existing research gap by concentrating on the Malaysian mobile phone services industry. A total of 550 of mobile phone users consisting of complainers and non-complainers from two selected states in Malaysia were selected as respondents. Using Structural Equation Modelling (SEM) to analyze the data, the GOF, AVE, CR and convergent validity values confirmed the measurement model of the CCB dimensions which consist of public complaint soft action, public complaint extreme action, private complaint soft action and private complaint extreme action for complainers and non-complainers, respectively. The structural model revealed mixed results of the relationships between the exogenous and endogenous variables. The results provide the indicator of the relationship quality between service providers and consumers. As the mobile phone services industry involves a huge number of Malaysian population this issue should become the focal point to the parties concerned in protecting the consumers.